1997
DOI: 10.1074/jbc.272.34.21060
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Specific Major Histocompatibility Complex Class I-restricted Epitope by Ubiquitin-dependent Degradation of Modified Ovalbumin in Lymphocyte Lysate

Abstract: Peptide epitopes presented through class I major histocompatability complex (MHC class I) on the cell surface, are generated by proteolytic processing of proteinantigens in the cytoplasm. The length and amino acid sequence determine whether a given peptide can fit into the peptide binding groove of class I heavy chain molecules and subsequently be presented to the immune system. The mode of action of the processing pathway is therefore of great interest. To study the processing mechanism of MHC class I-restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…5A, lane 3). Methylated ubiquitin typically leads to the accumulation of low molecular weight protein-ubiquitin conjugates (Ben-Shahar et al, 1997;Pickart and Vella, 1988), whereas ubiquitin aldehyde prevents the breakdown of multiubiquitin conjugates (Dang et al, 1998). The presence of these potential ubiquitin-CPEB conjugates in immature oocytes suggests that the ubiquitination machinery is functioning.…”
Section: Discussionmentioning
confidence: 99%
“…5A, lane 3). Methylated ubiquitin typically leads to the accumulation of low molecular weight protein-ubiquitin conjugates (Ben-Shahar et al, 1997;Pickart and Vella, 1988), whereas ubiquitin aldehyde prevents the breakdown of multiubiquitin conjugates (Dang et al, 1998). The presence of these potential ubiquitin-CPEB conjugates in immature oocytes suggests that the ubiquitination machinery is functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the proteasome in the production of MHC class I peptides was originally stressed by the observation that the presentation of the model antigen, ovalbumin, was dependent on ubiquitination and, therefore, on the 26S proteasome [ 14 , 15 ]. In line with this, MHC class I presentation was accelerated when the N-terminus of protein antigens was genetically modified with a bulky or a charged residue to increase their rate of ubiquitination by the ubiquitin ligase E3 α (N-end rule) [ 16 , 17 , 18 ].…”
Section: Role Of the Proteasome In Antigen Processingmentioning
confidence: 99%
“…Manipulation of genes that encode for antigenic proteins in a manner that renders the proteins more susceptible to ubiquitin-mediated degradation (such as conversion of the N-terminal amino acid residue into a "destabilizing" moiety) demonstrated that ubiquitin conjugation is a rate-limiting step in antigen presentation (295). Ben-Shahar et al (296) showed that production of SIINFEKL in a cell-free system from lymphocytes is mediated by the ubiquitin system: The process required ATP and ubiquitin, and could be reversibly inhibited by methylated ubiquitin. The in vitro experimental system may allow analysis of other components that may be involved in the process, such as molecular chaperones, which may be required to escort the generated peptides to the ER transport machinery, thus protecting them from cellular peptidases.…”
Section: Diverse Functions Of the Ubiquitin Systemmentioning
confidence: 99%